Amazon rainforest modulation of water security in the Pantanal wetland - Bergier, Ivan; Assine, Mario L. [UNESP]; McGlue, Michael M.; Alho, Cleber J. R.; Silva, Aguinaldo; Guerreiro, Renato L.; Carvalho, Joao C. (Elsevier B.V., 2018)
The Pantanal is a large wetland mainly located in Brazil, whose natural resources are important for local, regional and global economies. Many human activities in the region rely on Pantanal's ecosystem services including cattle breeding for beef production, professional and touristic fishing, and contemplative tourism. The conservation of natural resources and ecosystems services provided by the Pantanal wetland must consider strategies for water security. We explored precipitation data from 1926 to 2016 provided by a regional network of rain gauge stations managed by the Brazilian Government. A timeseries obtained by dividing the monthly accumulated-rainfall by the number of rainy days indicated a positive trend of the mean rate of rainy days (mm/day) for the studied period in all seasons. We assessed the linkage of Pantanal's rainfall patterns with large-scale climate data in South America provided by NOAA/ESRL from 1949 to 2016. Analysis of spatiotemporal correlation maps indicated that, in agreement with previous studies, the Amazon biome plays a significant role in controlling summer rainfall in the Pantanal. Based on these spatiotemporal maps, a multi-linear regression model was built to predict the mean rate of summer rainy days in Pantanal by 2100, relative to the 1961-1990 mean reference. We found that the deforestation of the Amazon rainforest has profound implications for water security and the conservation of Pantanal's ecosystem services. (c) 2017 Elsevier B.V. All rights reserved.
Keywords: Deforestation; Ecohydrology; Evapotranspiration; Ecosystem services; Global warming